Changes in rural development policy - the new development paradigm - Lorber, Lučka (Journal for Geography, 2013)
The purpose of this article is presenting the new rural development paradigm. For the new approaches to be understood and the effects of the new paradigm to be to analysed, the new paradigm should be explained and substantiated by critical comparison with the old paradigm. Numerous, mostly foreign authors, involved in theoretical as well as practical development of agriculture and rural areas, note that the success of the new paradigm directly depends on both, political will at the multi-institutional level as well as on readiness to accept new guidelines. Globally, the bottom-up approach has become established. Agriculture as an economic sector is no longer in the forefront. Changes in rural areas development paradigm started to emerge in the second half of the Twentieth century as a consequence of de-industrialisation effects and after the enlargement of the EU to the Mediterranean countries. By Agenda 2000, Leader programmes, the foundations were laid for the new development paradigm which became global in 2006 by publishing the new OECD rural development paradigm. In the conclusion, we were interested in the response of Slovenian rural policy to these changes and in the reasons for slow implementation of new approaches towards development of agriculture and rural areas.
Keywords: balance regional development; rural; Leader program; EU; OECD; new rural policy; Slovenia